Study of Chemical And Organoleptic of Sea Urchin Nugget Gonad By Filled of Sago Flour compound - Masuku, Mustamin Anwar; Rasulu, Hamidin; Sangaji, Samsa (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
In Indonesia, sea urchin gonads are consumed steamed, fried, baker or in a raw state, processed such as fermented pasta, bluder cake, fried cake, nuggets. This study aims properties the chemical and organoleptic properties of sea urchin nuggets with sago flour as a filler. This research method uses a simple randomized complete design (CRD) one factor consisting of 5 treatments and 3 replications so as to obtain 5x3-15 units of experiment. The treatmen consisted of 5 treatmens, namely sea urchin gonads 95% and sago flour 5% (N0), Sea urchin gonads 90% and sago flour 10% (N1), Sea urchin gonads 85% and sago flour 15% (N2), Sea urchin gonads 80% and sago flour 20% (N3), Sea urchin gonads 75% and sago flour 25% (N4). The parameters observed include chemical properties, namely water content, ash contend, fat content, protein content, carbohydrate content and total dissolved solids while for organoleptic properties include color, aroma, texture and taste. Sea urchin gonads and sago flour gave significantly different effects on water content, ash content, color, aroma, texture and taste. The best treatment for sea urchin gonads 75% and sago flour 25% (N4).